The given function is,
![j(x)=(-6x^3+2x)/(5x^2-3)\text{ ---(1)}](https://img.qammunity.org/2023/formulas/mathematics/college/50mekmu4oh9b6i5eyjxknxtqxyitz7pbkv.png)
To find j(0), substitute x=0 in expression (1).
![\begin{gathered} j(0)=(-6\cdot0^3+2\cdot0)/(5\cdot0^2-3)\text{ } \\ j(0)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wif3cxsp9wqw5uykpddsuuwgz1x0qzha7m.png)
So, j(0)=0.
To find j(2), substitute x=2 in expression (1).
![\begin{gathered} j(2)=(-6\cdot2^3+2\cdot2)/(5\cdot2^2-3)\text{ } \\ j(2)=(-6\cdot8+4)/(5\cdot4-3) \\ j(2)=(-48+4)/(20-3) \\ j(2)=(-44)/(17) \\ j(2)=-2(10)/(17) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gcg8vv0tvj1o6b6pmqy3qsaq1rjg6l2s6v.png)
Therefore, j(2)=-2 10/17.
To find j(-2), substitute x=-2 in expression (1).
![\begin{gathered} j(-2)=(-6\cdot(-2)^3+2\cdot(-2))/(5\cdot(-2)^2-3)\text{ ---(1)} \\ j(-2)=(-6\cdot(-8)-4)/(5\cdot4-3) \\ j(-2)=(48-4)/(20-3) \\ j(-2)=(44)/(17) \\ j(-2)=2(10)/(17) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sdff3rd127842b8txs6f622k6q6swu7vpd.png)
Therefore, j(-2)=2 10/17.
So, the obtained values are,
![\begin{gathered} j(0)=0 \\ j(2)=-2(10)/(17) \\ j(-2)=2(10)/(17) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vappk4io84wo5uy5rafdgulyitvja7utjv.png)
Comparing the values of j(0), j(2) and j(-2), we get
j(2)
Therefore, the statement j(-2)> j(0) is correct.